The Glycosylphosphatidylinositol Anchor: A Linchpin for Cell Surface Versatility of Trypanosomatids - Borges, Alyssa R.; Link, Fabian; Engstler, Markus; Jones, Nicola G. (Frontiers in Cell and Developmental Biology, 2021)
The use of glycosylphosphatidylinositol (GPI) to anchor proteins to the cell surface is widespread among eukaryotes. The GPI-anchor mediates the attachment of the C-terminus of a protein to the outer leaflet of the lipid bilayer by means of a covalent bond. GPI-anchored proteins have a wide range of functions, including acting as receptors, transporters, and adhesion molecules. In unicellular eukaryotic parasites, abundantly expressed GPI-anchored proteins are major virulence factors, which support infection and survival within distinct host environments. While, for example, the variant surface glycoprotein (VSG) is the major component of the cell surface of the bloodstream form of African trypanosomes, procyclin is the most abundant protein of the procyclic form in the invertebrate host, the tsetse fly vector. Trypanosoma cruzi also displays a high number of GPI-anchored molecules, such as mucins, on their cell surface, which interact with the different hosts. This is also true for Leishmania, which use GPI anchors to display, amongst others, lipophosphoglycans on their surface. Clearly, GPI-anchoring is a common feature in trypanosomatids and the fact that it has been maintained throughout eukaryote evolution indicates its adaptive value. Here, we explore and discuss GPI anchors as universal evolutionary building blocks supporting the great variety of surface molecules of trypanosomatids.